The relationship between payer type and lipid outcomes in response to clinical lifestyle interventions in youth with dyslipidemia - Jacob C. Hartz; Elizabeth Yellen; Annette Baker; Justin Zachariah; Heather Ryan; S. Skylar Griggs; Nirav K Desai; Ravi Yanumula; Samuel Vinci; Caroline Brantley; Jennifer Bachman; Ellen McAuliffe; et al. (BMC, 2019)
Abstract Background Payer-type (government-sponsored health coverage versus private health insurance) has been shown to influence a variety of cardiovascular disease outcomes in adults. However, it is unclear if the payer-type impacts the response to a lifestyle intervention in children with dyslipidemia. Methods We analyzed data prospectively collected from patients under the age of 25 years who were referred to a large regional preventive cardiology clinic from 2010 to 2016 in Massachusetts. We compared baseline high density lipoprotein cholesterol (HDL-C), triglycerides (TG), non-HDL-C, and low density lipoprotein cholesterol (LDL-C) by payer-type. Further, we analyzed the change in lipid values in response to a clinic-based multidisciplinary intervention over a nearly six-year period by payer-type with multi-variable adjusted linear regression models. We also tested for effect modifications by age, sex, race, and body mass index (BMI) category. Results Of the 1739 eligible patients (mean age 13 years, 52% female, 60% overweight and obese, 59% White), we found that patients with government-sponsored coverage (n = 354, 20%) presented to referral lipid clinic with lower HDL-C (− 3.5 mg/dL [1.0], p < 0.001) and higher natural log-transformed TG (+ 0.14 [0.04], p < 0.001) as compared to those with private insurance; however, the association was attenuated to the null after additionally adjusting for BMI category (− 1.1 [0.9], p = 0.13, and + 0.05 [0.04], p = 0.2 for HDL-C and natural log-transformed TG, respectively). We found no difference in baseline LDL-C between payer-types (+ 3.4 mg/dL [3.0], p = 0.3). However, longitudinally, we found patients with private insurance and a self-reported race of White to have a clinically meaningful additional improvement in LDL-C, decreasing 12.8 (5.5) mg/dL (p = 0.02) between baseline and first follow-up, as compared to White patients with government-sponsored health coverage, after adjusting for age, sex, time between visits, and baseline LDL-C. Conclusions Our results suggest that youth with government-sponsored coverage are referred with poorer lipid profiles than those with private insurance, although this is largely explained by higher rates of overweight and obesity in the government-sponsored health coverage group. White patients with private insurance had substantially better improvement in LDL-C longitudinally, suggesting that higher socioeconomic status facilitates improvement in LDL-C, but is less beneficial for HDL-C and triglyceride levels.